Knowledge, practices, and perceptions about tooth whitening among female population in Saudi Arabia - A cross-sectional study - Hani Sabri Jaha; Hajer Ayed Alhejoury; Amal Abdelrahman Fayad; Ayoob Mutleb Alnafisah; Ibrahim Alhosain Bahshan; Saud Ismail Assiri; Ahmed Salem Alsubhi (Wolters Kluwer Medknow Publications, 2021)
Background: Tooth-whitening procedures have gained wide popularity among the Saudi population. The present study aimed to assess the knowledge, attitude, and perception about tooth-whitening procedures among Jeddah's general population. Materials and Methods: A face-to-face interview was conducted on randomly selected female patients attending dental clinics. A pretested and structured questionnaire was used to record the response by calibrated interviewers. The responses regarding knowledge, attitude, and perceptions were recorded and subjected to statistical analysis. Results: The findings showed that the prevalence of tooth whitening among the participants was 43.7%, and about 8.7% reported that they did it once every year. In-office bleaching was the most preferred method (31.4%), followed by whitening toothpaste (8.7%). An increased frequency of bleaching was reported by participants belonging to younger age group (P < 0.001). Conclusion: The knowledge related to the mechanism of action and adverse effects was average among the participants. Younger age groups were more concerned about tooth-whitening procedures compared to the older ones.